Corrosion properties of aluminum-based alloys used in building constructions for different purposes - Grechanyuk, Vira; Matsenko, Oleksandra; Chornovol, Victoriya; Grechanyuk, Igor (Transfer of innovative technologies, 2023)
The corrosion resistance of an aluminium alloy АD 31, that is used in building constructions, is investigated. The connection between change of samples weight and time of corrosion tests is established. It is shown, that the corrosion is accompanied by simultaneous course of two processes: by oxide film formation and dissolution of more active metal. The temperature dependences have shown, that with the temperature increase higher 80°С the corrosion resistance is reduced. The accounts of weight and deep parameters of corrosion are made.